2008
DOI: 10.1063/1.2828702
|View full text |Cite
|
Sign up to set email alerts
|

Selective formation of Ohmic junctions and Schottky barriers with electrodeposited ZnO

Abstract: Constant-potential electrochemical synthesis of ZnO on metal substrates enables selective formation of either Ohmic or Schottky-barrier contacts. Using a mildly acidic nitrate-based aqueous electrolyte, there is a substrate-dependent deposition potential below which electrodeposited ZnO heterojunctions display Schottky response with high contact resistances (∼105Ω) and above which Ohmic behavior and low contact resistances (∼1Ω) occur. Voltammetric evidence for Zn metal deposition, in conjunction with Schottky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
(39 reference statements)
3
22
1
1
Order By: Relevance
“…(This hydrophobicity, consistent with other reports, 35 is due in part to the surface roughness of the electrodeposits. 19,24 ) Assessments of coating continuity and thickness using AFM showed that the hydrophobic layers appear continuous on length scales greater than ∼ 100 nm and typically vary in thickness from 10-60 nm. Pooling of the coating mixture does occur in deep features of the deposit, leading to substantially thicker coatings in some places.…”
Section: Surface Coating Effects On Rectificationmentioning
confidence: 99%
“…(This hydrophobicity, consistent with other reports, 35 is due in part to the surface roughness of the electrodeposits. 19,24 ) Assessments of coating continuity and thickness using AFM showed that the hydrophobic layers appear continuous on length scales greater than ∼ 100 nm and typically vary in thickness from 10-60 nm. Pooling of the coating mixture does occur in deep features of the deposit, leading to substantially thicker coatings in some places.…”
Section: Surface Coating Effects On Rectificationmentioning
confidence: 99%
“…Figure 4 shows that ohmic ZnO/substrate contacts form at more positive deposition potentials (with resistances of 1-10 Ω), while rectification occurs in samples prepared at more negative deposition potentials (with resistances of 10 5 -10 6 Ω), consistent with earlier findings. 24 There is also an intermediate range of deposition potentials for which either ohmic response or poor rectification (with pronounced soft breakdown) can result; in other words, there is poor selectivity between linear and rectifying behaviors for these deposition potentials. Nevertheless, the current-voltage response of any single sample is repeatable and does not .…”
Section: Effects Of Synthesis Conditions On Rectifying Behaviormentioning
confidence: 99%
“…This pH increase allows the formation of Zn(OH) 2 on the surface of the working electrode, which spontaneously decomposes to ZnO at temperatures above 50 • C. 16,18 Previous work from our group addressed the synthesis conditions required for ZnO electrodeposits displaying either ohmic or rectifying contacts with the underlying conducting metal substrates. 24 In the present work, we identify an expanded range of deposition conditions that can be used to synthesize rectifying ZnO contacts -with dramatically improved performance -by adjusting electrolyte pH. Samples were deposited at potentials ranging from -2.0 V to -0.…”
Section: Zno Electrosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Control over ZnO electrodeposit epitaxy, texture, morphology, carrier concentration, and orientation has been demonstrated, 2,4 as has selectivity between purely resistive (Ohmic) or rectifying (Schottky) electrical responses. 5,6 Here, we show that electrodeposited rectifying ZnO junctions, fabricated using a well-characterized nitrate reduction route, 3 have spatial (lateral) inhomogeneities that are not apparent using common characterization techniques such as X-ray diffraction or scanning electron microscopy. The origin of this effect is related to incomplete conversion of Zn 2+ to ZnO on some parts of the working electrode during the multi-step electrochemical synthesis process.…”
mentioning
confidence: 99%